What naturalistic stimuli tell us about pronoun resolution in real-time processing - Repp, Magdalena; Schumacher, Petra B. (Frontiers in Artificial Intelligence, 2023)
Studies on pronoun resolution have mostly utilized short texts consisting of a context and a target sentence. In the current study we presented participants with nine chapters of an audio book while recording their EEG to investigate the real-time resolution of personal and demonstrative pronouns in a more naturalistic setting. The annotation of the features of the pronouns and their antecedents registered a surprising pattern: demonstrative pronouns showed an interpretive preference for subject/agent antecedents, although they are described to have an anti-subject or anti-agent preference. Given the presence of perspectival centers in the audio book, this however confirmed proposals that demonstrative pronouns are sensitive to perspectival centers. The ERP results revealed a biphasic N400 – Late Positivity pattern at posterior electrodes for the demonstrative pronoun relative to the personal pronoun, thereby confirming previous findings with highly controlled stimuli. We take the observed N400 for the demonstrative pronoun as an indication for more demanding processing costs that occur due to the relative unexpectedness of this referential expression. The Late Positivity is taken to reflect the consequences of attentional reorientation: since the demonstrative pronoun indicates a possible shift in the discourse structure, it induces updating of the discourse structure. In addition to the biphasic pattern, the data showed an enhanced positivity at frontal electrode sites for the demonstrative pronoun relative to the personal pronoun. We suggest that this frontal positivity reflects self-relevant engagement and identification with the perspective holder. Our study suggests that by using naturalistic stimuli, we get one step closer to understanding the implementation of language processing in the brain during real life language processing.